Entrepreneurship teaching for children and vulnerable teenagers - Aveni, Dr. Alessandro (2019)
The research discusses three Brazilian proposals in teaching entrepreneurship to children and adolescents. The objective is to verify the proposals from the point of view of active practices and successively on the viability of the proposal for low income and vulnerable population. The result shows advances in proposals and practices with some limitations. However, in relation to education for low-income and vulnerable sectors, no specific proposal was found, but generic and therefore not adequate. The work may advance with the analysis of practices of third sector organizations that are identified as possible entities whose activity close to low income and vulnerability cases may result in viable practices. However, the focus of these proposals should be related to family entrepreneurship oriented to an autonomous profession and to formalize these enterprises.